Antimicrobial use of patients with sexually transmitted infection symptoms prior to presentation at five health facilities in Southern Ghana - Attram, Naiki; Dela, Helena; Behene, Eric; Kyei, Nicholas N. A.; Ocansey, Karen; Yanney, Jennifer N.; Nyarko, Edward O.; Addo, Kennedy K.; Koram, Kwadwo A.; Fox, Anne; Letizia, Andrew; Sanders, Terrel (Antimicrobial resistance and infection control, 2023)
Unregulated and inappropriate antimicrobial use are major contributors to the evolution of antimicrobial resistance worldwide. It is important to monitor and collect data on the use of antibiotics at health facilities and in the general population in order to support antimicrobial stewardship programs.
Published: 13 December 2023
Gesehen am 30.09.2024